Perceptions of the teaching digital competence of secondary education teachers in Havana - Carballo Soca, Alberto Antonio (2024)
The objective of this research is to analyze the perceptions of teaching digital competence of secondary education teachers in Havana, focusing on their knowledge, skills and attitudes in the areas of professional engagement, digital resources, digital pedagogy, evaluation and feedback, empowering students and facilitating students' digital competence. For this purpose, a qualitative phenomenological study was carried out through an in-depth individual interview with a sample of 12 teachers. The results reflect that teachers perceive themselves as having better knowledge, skills and attitudes in the area of professional engagement, emphasizing the use of digital technologies for communication and collaboration. The perception of limited knowledge and skills is particularly evident in the core pedagogical areas of digital teaching competence and in those focused on developing students' digital competence. The study concludes by highlighting the importance of raising teachers' awareness among teachers of the need to facilitate the digital competence of students and to develop digital competences in the areas of the pedagogical core for better use of digital technologies in the teaching and learning processes.